PENGEMBANGAN APLIKASI PENJUALAN FURNITURE BERBASIS CUSTOMER RELATIONSHIP MANAJEMENT (CRM) PADA PLATFORM ANDROID - Fajarwibowo, Dhimas; Muhimmah, Izzati (Jurnal Teknik Informatika dan Komputer, 2024)
Trends in interior design, modern lifestyles, and increasing consumer awareness about the beauty and comfort of the home have driven the ever-increasing demand for quality furniture products. In this context, furniture companies are required to not only produce attractive products but also provide superior and personal service to customers. To overcome various challenges in the furniture industry, this research developed a CRM-based furniture sales application on the Android platform. The application is expected to be a solution to improve service to customers. The features provided include displaying furniture stock info along with prices, search features, furniture ordering features, transactions, purchase history, features for analyzing customer preferences based on product type criteria, and shipping. The methods used include literature studies, site surveys where the application will be used, needs analysis, application design, application development, implementation, and testing. The results of functionality testing show that the application has functioned as expected.